2014
DOI: 10.1039/c4nr04602a
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of monolayer MoS2on LaAlO3and SrTiO3substrates

Abstract: In an atomically thin-film/dielectric-substrate heterostructure, the elemental physical properties of the atomically thin-film are influenced by the interaction between the thin-film and the substrate. In this article, utilizing monolayer MoS(2) on LaAlO(3) and SrTiO(3) substrates, as well as SiO2 and Gel-film as reference substrates similar to previously reported work [Nano Res, 2014, 7, 561], we systematically investigate the substrate effect on the photoluminescence of monolayer MoS(2). We observed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 41 publications
8
114
1
Order By: Relevance
“…In the last two decades, materials including thin films with metal and non-metals oxides have been actively studied (Li et al 2014;Ohnishi et al 2004;Zawadzka et al 2014a;Nomura et al 2001). One of the main goals of these studies was finding the films with specific properties which allow using them as buffer layers.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, materials including thin films with metal and non-metals oxides have been actively studied (Li et al 2014;Ohnishi et al 2004;Zawadzka et al 2014a;Nomura et al 2001). One of the main goals of these studies was finding the films with specific properties which allow using them as buffer layers.…”
Section: Introductionmentioning
confidence: 99%
“…Interference has an impact on the absorption and emission intensities but has no relation to the peak position. It is also found that Raman modes are more related to the strain caused by the substrate instead of doping and dielectric screening [21]. Research on other transition-metal dichalcogenide (TMD) materials, such as MoSe2 and WS2, has shown similar properties.…”
Section: A + ↔mentioning
confidence: 66%
“…For example, at the MoS2/glass interface, the first principle calculations show that Na atoms in the glass might become donors to make the system an n-type semiconductor, while the O dangle bonds could do the opposite because of the opposite charge polarity [16]. Li et al utilized different substrates including LaAlO3, SrTiO3, and SiO2 to control the charge transfer between a substrate and a monolayer of MoS2 [21]. A model is set up to explain how the Fermi level and work function of the substrate influence the charge transfer.…”
Section: D Semiconductors/traditional Dielectric Materials Heterostrumentioning
confidence: 99%
“…Electrical gating of two-dimensional materials increases photoluminescence intensity, whereas the photoluminescence wavelength remains nearly constant [30]. The photoluminescence of a two-dimensional material is strongly affected by the type of substrate where it is deposited [31]. Piezoelectric substrates such as SrTiO 3 have a higher emission intensity than dielectric substrates such as SiO 2 which reduces the emission intensity.…”
Section: Photoluminescencementioning
confidence: 99%